Research Progress of Olfactory Nerve Regeneration Mechanism and Olfactory Training - Hu B; Zhang J; Gong M; Deng Y; Cao Y; Xiang Y; Ye D (Dove Medical Press, 2022)
Bian Hu,1,2 Jingyu Zhang,3 Mengdan Gong,1 Yongqin Deng,1 Yujie Cao,1 Yizhen Xiang,1 Dong Ye1 1Department of Otorhinolaryngology-Head and Neck Surgery, Lihuili Hospital of Ningbo University, Ningbo, 315040, Zhejiang, People's Republic of China; 2Department of Otorhinolaryngology-Head and Neck Surgery, Ninghai First Hospital, Ningbo, 315699, Zhejiang, People's Republic of China; 3Shanghai Jiao Tong University, Shanghai, 200030, People's Republic of ChinaCorrespondence: Dong Ye, Department of Otorhinolaryngology-Head and Neck Surgery, Lihuili Hospital of Ningbo University, Ningbo, 315040, Zhejiang, People's Republic of China, Tel +86 13819861213, Fax +86 574-87392232, Email yedong518@sina.comAbstract: The olfactory nerve (ON) is the only cranial nerve exposed to the external environment. Hence, it is susceptible to damage from head trauma, viral infection, inflammatory stimulation, and chemical toxins, which can lead to olfactory dysfunction. However, compared with all other cranial nerves, the ON is unique due to its inherent ability to regenerate. This characteristic provides a theoretical basis for treatment of olfactory dysfunction. Olfactory training (OT) is one of the main treatments for olfactory dysfunction. It is easy to apply and has few side-effects, and has been shown to be efficacious for patients with olfactory dysfunction of various causes. To further understand the application value of ON regeneration and OT on olfactory dysfunction, we review the research progress on the mechanism of ON regeneration and OT.Keywords: olfaction, regeneration, olfactory training, olfactory dysfunction